2012
DOI: 10.5301/je.2012.9229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between GnRH agonist and antagonist protocols for severe endometriosis in assisted reproductive cycles

Abstract: Purpose Endometriosis may influence different aspects of reproductive physiology including folliculogenesis, ovulation, embryo quality, and fertilization. Recent data demonstrate that patients with endometriosis-associated infertility undergoing in vitro fertilization (IVF) have a reduction of pregnancy rates compared to women with other indications for IVF. The aim of the study is to evaluate the outcomes of IVF after controlled ovarian hyperstimulation (COH) with GnRH antagonist (GnRH-ant) or GnRH agonist (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…The number of retrieved oocytes, the number of obtained embryos, the implantation rates and the clinical pregnancy rates were similar with GnRH-ant and GnRH-a protocols. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…The number of retrieved oocytes, the number of obtained embryos, the implantation rates and the clinical pregnancy rates were similar with GnRH-ant and GnRH-a protocols. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] In these studies, 1721 cycles used the long GnRHagonist protocol and 1040 cycles used the GnRHantagonist protocol. Six retrospective analyses, [13][14][15][16][17]20 one cross-sectional study 18 and one RCT 19 were identified. Each study was undertaken at a single centre, and all inclusion/exclusion criteria were available.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies in the GnRHantagonist arm administered subcutaneous cetrorelix or ganirelix. [13][14][15][16][17][18][19] Five of which followed a flexible multiple dosing protocol 13,[15][16][17]19 and two of which followed a fixed protocol from day 5 or day 6. 14,18 One study also gave patients in the GnRH-antagonist arm an oral contraceptive pill pretreatment taken for 14-24 days in the preceding cycle followed by a 3-to 5-day washout period.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations